Development of Business Scale: Empirical Evidence from Business Center UINSA Surabaya - Akhmad Yunan Atho'illah; Ana Toni Roby Candra Yudha (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Responses and strategies for the enrichment of product marketing problems in business units at Universitas Islam Negeri Sunan Ampel (UINSA) Surabaya need to be done. It is reasonable to prepare considering that the COVID-19 pandemic has had a systemic impact on all sectors, including the economic and business sectors. Business units in universities as one of the sub-fields that need to be developed as incubation centers, and sources of income for universities are important to maintain stable performance. The purpose of this study was to determine the identification of internal and external conditions. The research used is qualitative, with a descriptive strategy and SWOT analysis as an analytical tool. Informants from this study came from internal and external institutions, such as the daily board (BPH), employees, and customers. Validation of data using in-depth interviews, in order to obtain the accuracy and validity of data and information. The results indicate that the internal and external SWOT analysis is located in quadrant 1, (0.026; 0.063), which shows the results that these coordinates place the company in a position that supports an aggressive strategy. A strategy that prioritizes sales focus and strengthens internal management. Then from an institutional managerial point of view, PUSBIS in its current condition also has fairly solid teamwork, protecting all members of the extended family by carrying out reading routines, daily financial evaluations, self-development training, and compensation for improving performance. Research suggestions that are in accordance with the results of the study are increasing sales skills, utilizing social media, marketplaces, and involving websites to launch and sell products. It is considered important and necessary in the midst of a pandemic that is still not over, to capture the normal potential of buyers from outside the campus.